Reinterpreting Buddhist Environmental Ethics Through the Lens of Agential Realism - Setiawan, Rezza Prasetyo (Satya Widya: Jurnal Studi Agama, 2023)
The reality of climate change and other environmental crises calls for a cooperative effort to ensure a more effective effort toward environmental sustainability. Buddhist environmental ethics sets an interesting departure to talk about environmental awareness because of its attention toward all living beings. However, there are critics accusing Buddhist environmental awareness of being too biocentric and ignorant to the socio-political aspect of environmental ethics. This article will give another perspective on Buddhist environmental ethics, by incorporating an onto-epistemological paradigm constructed by Karen Barad, which she calls Agential Realism. Further exploration on Buddhist environmental ethics from the Agential Realist perspective shows that the incorporation of multiple aspects in environmental struggle is possible, and even necessary.